2021
DOI: 10.1111/hsc.13333
|View full text |Cite
|
Sign up to set email alerts
|

Trans and Gender‐Diverse peoples’ experiences of crisis helpline services

Abstract: Crisis helplines are typically easily accessible and deliver interventions in a timely manner, regardless of geographical location. The efficacy and user experiences of these services are the subject of considerable interest within the field, but the experiences of trans and gender-diverse individuals remain unexplored despite high rates of mental ill health being documented in this population. A total of 134 trans and

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 71 publications
0
6
0
Order By: Relevance
“…Improving trans affirmative practice in health services is also important for reducing suicide risk. Previous studies have identified that structural stigma and a subsequent lack of education regarding trans health and gender affirmation among medical professionals, allied health, and nursing staff have led to a limited number of health providers and crisis support providers, including telephone support lines, who are competent in providing appropriate trans healthcare in Australia (Dolan et al, 2020;Lim et al, 2021;Poteat et al, 2013). This may result in potential pathologizing of trans individuals seeking care, leading to a delay in seeking medical treatment and increasing distress (Cruz, 2014) may present with different experiences and needs.…”
Section: Discussionmentioning
confidence: 99%
“…Improving trans affirmative practice in health services is also important for reducing suicide risk. Previous studies have identified that structural stigma and a subsequent lack of education regarding trans health and gender affirmation among medical professionals, allied health, and nursing staff have led to a limited number of health providers and crisis support providers, including telephone support lines, who are competent in providing appropriate trans healthcare in Australia (Dolan et al, 2020;Lim et al, 2021;Poteat et al, 2013). This may result in potential pathologizing of trans individuals seeking care, leading to a delay in seeking medical treatment and increasing distress (Cruz, 2014) may present with different experiences and needs.…”
Section: Discussionmentioning
confidence: 99%
“…Even with evidence of elevated rates of mental distress among LGBTQ populations, many queer community members in high-income countries find it difficult to access adequate mental health services (Higgins et al, 2021 ; Lim et al, 2021a , b ). LGB individuals in Australia report minority-related stress, finances and time constraints as barriers to accessing help (Cronin et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…In this sense, expanding demographic reporting to be inclusive of nonbinary gender is essential. A recent study (Lim et al, 2021) of the experiences of gender fluid callers to a crisis hotline in Australia found that these callers preferred to avoid the hotline, citing that responders were not appropriately able to recognize or support the specific mental health needs of gender minorities. This is a call for crisis services to adapt to better understand and address the concerns of gender-diverse individuals; part of this task is to broaden the scope of understanding of gender.…”
Section: Discussionmentioning
confidence: 99%
“…A small number of the reviewed studies reported on the outcomes of calls to crisis hotlines, with some indicating gender differences in these outcomes. The majority of studies that assessed call outcome focused on reporting suicide mortality rates (Chan et al , 2018; Hanneman et al ,2021; Ramsey et al , 2019; Shaw and Chiang, 2019). Other studies reported on the decrease in suicidal intent or absence of a suicide event following a call (Gould et al , 2007, 2016; Mishara et al , 2007, 2016; Witte et al , 2010).…”
Section: Outcomes Of Crisis Calls By Gendermentioning
confidence: 99%